CP-TruPeC / Ida Hasni Shaari … [et al.] - Shaari, Ida Hasni; Jathin, Romizan; Jamaluddin, Bahman; Md Yunus, Nur Farhana; Jafri Sham, Mohd Shukree (Research Innovation Business Unit, 2014)
The ability to rise from sitting can be considered as one of the most common movements and a fundamental transition to acquired functional activities (Da Costa et al., 2013). This transition requires good body segmental alignment in order to maintain an upright posture (Kouta, Shinkoda & Kanemura, 2006). A cerebral palsy child however shows difficulty in performing this activity as they developed a poor body alignment, abnormal muscle tone and muscle weakness (Dos Santos et al., 2011). This impairment makes them develop various compensatory movements (Park et al., 2003). Previous studies found that those compensatory patterns might lead to deviation of the normal kinematics pattern (Reid, Elliot, Alderson et al., 2010; Piccinini et al., 2011). The application of orthosis together with physiotherapy session is commonly apply to overcome the mal-alignment on the child’s posture (Radtka, Skinner & Johanson, 2005). Rigid thesis such as AFO has found to be effective in increasing range of motion in the knee and ankle of CP child (Lykissas & McCarthy, 2013). This indicates that the hinged AFO did provide structural support to the knee and ankle during the STS task. However, none of the previous studies have indicated any changes on the pelvis and hip angular motion for STS with AFO and without AFO. A possible reason could be; the AFO is only giving support on the distal structural alignment rather than the proximal joints which is the pelvis and hip (Park et al., 2004). Therefore, the application of another orthsosis may correct the pelvis and spine alignment during STS motion. Other than AFO, Sitting, Standing and Walking Hip Orthosis (SWASH) has also been used to enhance transition and mobility level in CP children (Boyd, Dobson, Parrott et al., 2001). However, the effectiveness of this device was unclear. This is due to limited study has investigated the effects of SWASH application on the STS ability in CP children. Improvement on the material and concept of orthosis application initiated the development of undergarment orthsosis such as TheraTogs and Lycra garment (Ibuki et al., 2010). The application of garment orthosis on CP child has found to improve bone and joint alignment, improves the patient’s functional activity level (Richards et al., 2012). Compared with the rigid orthosis, the undergarment orthosis was found to be more clinically beneficial as the undergarment allows multiple segmental corrections at the same time allows the child to move actively. However, for the SWASH, no studies have investigated the effectiveness on this soft orthosis in providing spine-pelvis correction, and improving the STS ability in CP children. Therefore, a better design orthosis could possibly enhance the STS ability in CP children. Thus, this project adds additional value on the current orthosis device to enhance the spine-pelvis alignment at the same time improving the CP child STS ability. This project combines the concept of rigid orthosis which is SWASH with soft orthsosis, TheraTogs to produce device that could improve the child STS ability by providing correction on the spine-pelvis alignment.